Evolution of public administration and its implication to management and business education - Kadakure, Arthur; Twum-Darko, Michael (Journal of Management and Business Education, 2024)
The paper offers a thorough analysis of the historical development of public administration, aiming to gain deeper insights into the current challenges facing the discipline. Utilizing an evolutionary theoretical lens, the study sheds light on the transitional development of Public Administration (PA). Additionally, it discusses the New Public Administration (NPA) and its implications for the integrity of the public administration discipline. Through a comprehensive review of literature, the paper establishes that despite the logical progressions of public administration presented in literature, there is evidence of a recurring identity crisis within the discipline, with significant implications for business education. Furthermore, the paper proposes an ideal concept of a lesson on Public Administration based on current literature, while examining the notion of the dichotomy between political science and public administration. It also argues that the theoretical framework underpinning the development of public administration is likely to evolve due to the dynamic societal consciousness that shapes this discipline. Ultimately, the paper suggests a theoretical framework that may gain traction in management and business education by combining the founding principles of public administration with the contemporary emerging needs of a transitional industrial order.